Physical aging in amorphous poly(ethylene furanoate): Enthalpic recovery, density, and oxygen transport considerations. Issue 6 (15th December 2014) - Burgess, Steven K.; Mubarak, Christopher R.; Kriegel, Robert M.; Koros, William J.
ABSTRACT The current work utilizes three separate techniques to study the physical aging process in amorphous poly(ethylene furanoate) (PEF), which is a recently introduced engineering thermoplastic with enhanced properties compared to petroleum‐sourced poly(ethylene terephthalate). Differential scanning calorimetry aging experiments were conducted at multiple aging temperatures and times, and the resultant enthalpic recovery values compared to the theoretical maximum enthalpy loss evaluated from calculations involving extrapolation of the equilibrium liquid line. Density measurements reveal densification of the matrix for the aged versus unaged samples, and provide an estimate for the reduction in free volume for the aged samples. Complementary oxygen permeation and pressure‐decay sorption experiments provide independent verification of the free volume reduction mechanism for physical aging in glassy polymers. The current work provides the first detailed aging study for PEF. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 389–399